2012
DOI: 10.1111/j.1540-8167.2012.02317.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic Effects of Vasostatin‐1 in a Canine Model of Atrial Fibrillation

Abstract: Vasostatin-1 suppresses AF inducibility, likely by inhibiting GP function. These data may provide new insights into the role of peptide neuromodulators for AF therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 38 publications
0
27
1
Order By: Relevance
“…The discrepancies in the results among these studies can to some extent be explained by the stimulation protocol, the stimulation intensity and frequency, the following time, and the small number of patients involved in these studies. It is important to mention that recent experimental evidence has indicated that different levels of parasympathetic stimulation release different neurotransmitters, which affect cardiac pathologies [21][22][23]. For example, Stavrakis et al [21,22] have shown that lowlevel VNS, well below that which slows the heart rate, that is, via acetylcholine release, suppresses AF associated with the anti-adrenergic action of vasostatin-1 and the nitric oxide signaling pathway.…”
Section: Es-pns and Hfmentioning
confidence: 99%
See 2 more Smart Citations
“…The discrepancies in the results among these studies can to some extent be explained by the stimulation protocol, the stimulation intensity and frequency, the following time, and the small number of patients involved in these studies. It is important to mention that recent experimental evidence has indicated that different levels of parasympathetic stimulation release different neurotransmitters, which affect cardiac pathologies [21][22][23]. For example, Stavrakis et al [21,22] have shown that lowlevel VNS, well below that which slows the heart rate, that is, via acetylcholine release, suppresses AF associated with the anti-adrenergic action of vasostatin-1 and the nitric oxide signaling pathway.…”
Section: Es-pns and Hfmentioning
confidence: 99%
“…It is important to mention that recent experimental evidence has indicated that different levels of parasympathetic stimulation release different neurotransmitters, which affect cardiac pathologies [21][22][23]. For example, Stavrakis et al [21,22] have shown that lowlevel VNS, well below that which slows the heart rate, that is, via acetylcholine release, suppresses AF associated with the anti-adrenergic action of vasostatin-1 and the nitric oxide signaling pathway. Others have shown that vaso-intestinal peptide, co-released with acetylcholine, can influence the propensity for AF [23].…”
Section: Es-pns and Hfmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, further studies in our experimental model of induced AF, showed that vasostatin-1 suppressed AF by inhibiting GP hyperactivity by an anti-autonomic action mediated by nitric oxide [93].…”
Section: Additional Supporting Studiesmentioning
confidence: 98%
“…Indeed, further studies in the experimental model of induced AF, showed that vasostatin-1 suppressed AF by inhibiting GP hyperactivity by an anti-autonomic action mediated by nitric oxide [86,87].…”
Section: Review Of Experimental Studiesmentioning
confidence: 99%